Graphic novels now : building, managing, and marketing a dynamic collection - Goldsmith, Francisca (American Library Association, 2005)
In 1992, Maus, a graphic novel by Art Spiegelman, won the Pulitzer Prize. The genre has been growing ever since, appealing to the visual-oriented Gen-X and Gen-Y, as well as to reluctant readers, those of all ages seeking alternative viewpoints, and anyone willing to take both image and word into consideration. Graphic Novels Now helps librarians new to the genre with all the key issues related to these unique books. Expert author Francisca Goldsmith shares smart advice, from how to develop a well-rounded collection by finding reviews and reliable publishers and distributors to shelving, catal.